AI in food industry automation: applications and challenges - Song, Xiaodong; Zhang, Xueru; Dong, Guanjun; Ding, Haohan; Cui, Xiaohui; Han, Yu; Huang, Huadi; Wang, Long (Frontiers in Sustainable Food Systems, 2025)
In automated production and processing technologies in the food industry, artificial intelligence (AI) plays a key role. The use of intelligent automation technology in multiple production processes not only greatly improves production efficiency, but also ensures the safety and quality of food products, which has great potential for the innovative revolution in the food industry. This paper provides an overview of AI technology and its potential applications in food industry automation, focusing on its use in food safety testing, production processing, production data analysis and prediction, and demonstrating the benefits of increased efficiency, reduced costs and improved product quality. However, the power of AI technology for the food industry has also prompted consideration of the possibilities and limitations of introducing intelligent food automation processing equipment or systems into food business applications. The aim of this paper is to provide ideas and guidance to governments, researches and food industry personnels in the hope of encouraging and accelerating the development of AI technology in food production and processing.